Comparison of biomechanical factors among straight, curve and knuckle kicking motions in soccer - Kimachi, K.; Liu, R.; Koido, M.; Hong, S.; Shimonagata, S.; Nakayama, M.; Asai, T. (Proceedings, 2020)
The rotation of a soccer ball is affected by several factors, such as impact point and foot posture, which are generated by joint torque in the lower limb. This study aimed to investigate joint torque in the lower limb that generates foot posture and swing trajectory, and compare three types of kicks before and after a practice period for participants to learn to control the ball rotation. An optical three-dimensional motion capture system was used to record the kicking motion of the participants. The results indicate that the adduction torque of the hip joint at the moment of impact decreased for curve kicks (from 0.56 to 0.25 Nm/kg) and increased for knuckle kicks (from -0.09 to 0.37 Nm/kg). We considered that the curve and knuckle kicks swing towards the inside (because of their positive values in the post experiment) with hip joint adduction before impact to control ball rotation.